2014
DOI: 10.1128/jvi.03376-13
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Central Nervous System Transduction with Lentiviral Vectors Pseudotyped with RVG/HIV-1gp41 Chimeric Envelope Glycoproteins

Abstract: To investigate the potential benefits which may arise from pseudotyping the HIV-1 lentiviral vector with its homologous gp41 envelope glycoprotein (GP) cytoplasmic tail (CT), we created chimeric RVG/HIV-1gp41 GPs composed of the extracellular and transmembrane sequences of RVG and either the full-length gp41 CT or C terminus gp41 truncations sequentially removing existing conserved motifs. Lentiviruses (LVs) pseudotyped with the chimeric GPs were evaluated in terms of particle release (physical titer), biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…In addition, lentiviral vector transduction of dendritic cells involved endosomal trafficking, and its efficiency was enhanced by suppressing autophagy (59). Indeed, we have recently reported an increase in retrograde transduction in the brain of lentiviral vectors pseudotyped with a chimeric RV-G bearing a portion of gp41 for its cytoplasmic tail (60). We have also observed that incorporation of different yet more efficient fusogens (61) in combination with surface-expressed antibodies targeting neuromuscular junction receptors onto the lentiviral vector surface enhances the ability of retrogradely transported vectors to transduce motor neurons within microfluidic motor neuron cultures following axonal chamber application (50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lentiviral vector transduction of dendritic cells involved endosomal trafficking, and its efficiency was enhanced by suppressing autophagy (59). Indeed, we have recently reported an increase in retrograde transduction in the brain of lentiviral vectors pseudotyped with a chimeric RV-G bearing a portion of gp41 for its cytoplasmic tail (60). We have also observed that incorporation of different yet more efficient fusogens (61) in combination with surface-expressed antibodies targeting neuromuscular junction receptors onto the lentiviral vector surface enhances the ability of retrogradely transported vectors to transduce motor neurons within microfluidic motor neuron cultures following axonal chamber application (50).…”
Section: Discussionmentioning
confidence: 99%
“…Lentivirus vector particles are usually pseudotyped with VSV G to enlarge their tropism, but also RABV G can be used to more specifically target neurons (Cronin et al, 2005;Trabalza et al, 2014). A fundamental difference between lentiviruses and (onco-) retroviruses like mouse leukemia virus (MLV) is the inability of the latter to transduce postmitotic cells like neurons.…”
Section: Retroviruses and Lentivirusesmentioning
confidence: 99%
“…In particular, HiRet (FuG-B/B2) and FuG-E are highly efficient at transduction and retrograde transport. [57][58][59][60] The G protein from a related Rhabdovirus, Mokola virus (MOKV-G), also shows similar ability to pseudotype LVs. MOKV infects cats and other sub-Saharan mammals, but rarely humans.…”
Section: Rhabdoviral Envelopesmentioning
confidence: 99%